(untitled) (GEOmedia, 2010)
Lombardy Geoportal Region Lombardy is setting up the regional SDI in the INSPIRE perspective, involving both local Public Administrations and the private sector in the process of disseminating and sharing the geographic data and services available in Lombardy. The access point of the regional SDI is the Lombardy Geoportal, a Web place where users can publish or search for geographic data, applications and services, view maps, download data and share their geographic knowledge. The Lombardy Geoportal has been implemented by customizing the ESRI GIS Portal Toolkit, in order to be compliant with the Italian and the INSPIRE needs; The Geoportal is built on top of REGIS, the Regional Enterprise platform for Geographic Information Services, which consists of an technological infrastructure (based on ESRI Enterprise components) and basic services to build up geographic solutions.